The effectiveness of plant protection products against Lobesia botrana Den. U Schift. in Zakarpattya - Yushchenko, L.; Fedorenko, V.; Lohoida, O.I. (Quarantine and plant protection, 2024)
Goal. To establish the effectiveness of chemical protection of vineyards against pests, taking into account the peculiarities of their biology, distribution, harmfulness, seasonal dynamics of flight in Zakarpattya Ukraine. Methods. The research was conducted in accordance with the generally accepted methods in entomology and viticulture in 2021—2022 on the basis of Chateau Chizay LLC. The dynamics of the pest’s flight were studied in the field using the pheromone monitoring method using «Atrakon» pheromone traps and synthetic sex pheromones from the company «Csalomon» (Hungary). The research was conducted on Muscat, Chersegui, Sovignon Blanc, Pinot Noir, Cabernet Sovignon, Merlot, Rhine Riesling, and Pino Blan varieties. In 2022, in the vineyards of Chateau Chizay LLC, Zakarpattia Oblast, chemical plant protection agents were tested against grape leaf curl: Karate Zeon 050 CS, SK (liambda-tsyhalotryn, 50 h/l), 0.65 l/ha, Korahen 20, KS (khlorantraniliprol, 200 h/l), 0.15 l/ ha, Mavrik, EV (tau-fliuvalinat, 240 h/l), 0.2 l/ha, Voliam Fleksi 300 SC, KS (tiametoksam, 200 h/l + khlorantraniliprol, 100 h/l), 0.3 l/ha according to generally accepted methods. Results. Prolonged spring cooling in 2022 delayed the start of the flight of the first generation of cluster leafhopper, which began only in the first days of May. The second generation of this pest has been actively developing since the end of June. Grape damage on different varieties ranged from 2.1% on Muscat to 8.0% on Pino Blan. In the control (not treated with insecticides) plots, this indicator averaged 96.1%. The yield in the farm by variety averaged about 8 t/ha and ranged from 7.1 t/ha for the Muscat variety to 9.0 t/ha for the Merlot variety. In the control plot, the yield was low, only 1.4 t/ha. The effectiveness of protective measures on all grape varieties reached 90.5%. Conclusion. It was established that the protracted spring cooling caused the late start of flight of the grape leafhopper, which made adjustments to the calendar of protective measures, especially chemical ones. At the same time, thanks to pheromone monitoring, it was possible to establish the exact date of the start of Lobesia botrana’s flight and specify the timing of the application of chemical insecticides at the most favorable time, which made it possible to achieve an efficiency of more than 90%. Use of plant protection products against Lobesia botrana Den. et Schiff. in vineyards, LLC «Chateau Chizay», Zakarpattia Oblast contributed to the reduction of grape damage up to 94% and the preservation of the harvest up to 6.5 t/ha.